A Critical Comparison of Whole School and Programme Level Cross Curricular Strategies and Their Relationship to the Design and Technology Curriculum in Three New Zealand Secondary Schools - Dingle, Abbie (Auckland University of Technology, 2018)
Cross curricular education is not a new concept and has more recently come into the spotlight as educators seek pedagogies to better prepare our students for the future. This study aims to identify cross curricular learning strategies currently in practice in New Zealand. The key aims sitting alongside this are to gather student and teacher perceptions of the practice, identify what is enabling and/or restricting cross curricular pedagogy and to identify sustainable cross curricular models. Despite the terminology associated with cross curricular learning being inconsistent, for the purposes of this study, the terms cross curricular learning and curriculum integration are used interchangeably to describe teaching and learning happening across two or more learning disciplines. To unpack the different approaches to cross curricular teaching and learning, a hierarchy of cross curricular approaches is used to help clarify its different facets. The key findings of the literature review reveal why cross curricular education is so beneficial to both students and teachers and the potential barriers which can restrict its implementation and growth. The research design for the study was a small-scale qualitative approach. With the study focusing on gathering perceptions of lived experiences, a qualitative paradigm was adopted to build and generate perceptions of cross curricular pedagogy. Data was gathered from three schools, interviewing both students and teachers in semi structured and focus group interviews. Interviews and focus groups were conducted to allow for both personal perceptions to be explained and to gather different insights from a group perspective. The study revealed that cross curricular learning strategies included collaboration, essential support in terms of leadership and logistics, real world curriculum and student agency. In many aspects, these strategies were not only the key elements in making cross curricular learning successful, but could also act as the elements which aided in its failure. Although more research is required into the sustainability of the cross curricular approach, the findings of this study will contribute to the literature on cross curricular education and inform the practice of educators interested in the pedagogy.
Keywords: Cross curricular; Integrated curriuclum; Cross curriuclar learning; Cross curricular strategies